The Role of the Younger Generation in Employment Absorption and the Export of Montong Durian Business on Change Management at Pt. Changtu Jaya Indonesia, Parigi Moutong Regency, Central Sulawesi - Awaludin; Ali Supriadi; Abdul Rahman; Latifa (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
PT. Changtu Jaya Indonesia. The villages of Dolago and Boyantongo in South Parigi Subdistrict have recruited local workers. Young men and women from the surrounding villages, approximately 200 people, met the following employment requirements: 1) young workers, 2) aged between 21 and 24 years old, 3) disciplined, 4) diligent, 5) obedient to orders. The research methods used were: 1) conducting a location survey, 2) interviewing workers, and 3) distributing questionnaires to the research subjects. Respondent identity: The female gender rate was dominant at 9 frequencies or (0.6)%, compared to the male gender rate of only (0.4)%. The highest age group was 21 to 24 years old = 10 frequencies or (0.67)%, and other ages (0.33)%. The dominant education level was senior high school = 8 frequencies or (0.54)%, and other education levels (0.46)%. The Role of Young People in Labour Absorption: Regarding workers ‘having a healthy physical condition’, 10 respondents strongly agreed or (0.067)%, and others (0.33). Regarding the availability of materials and goods, 9 respondents strongly agreed (0.6%) and the rest agreed (0.4%). Regarding the availability of short training courses, 8 respondents strongly agreed (0.53%) and the rest agreed (0.47%). Montong durian business exports: Regarding durian business exports ‘gaining large profits’, 13 respondents strongly agreed (0.87%), and the rest (0.13%). Regarding ‘business development’ facilities and infrastructure, strongly agree 10 frequencies or (0.67)%, and others (0.33)%. Regarding the opportunity for companies to open ‘isolated work areas for cooperation’, strongly agree 9 frequencies or (0.06), and others (0.4)%. Change management at PT.Changtu Jaya Indonesia: Regarding motivation to obtain rewards or career advancement, 10 respondents strongly agreed (0.67%), and the rest (0.33%) disagreed. Regarding moral motivation to work together, 8 respondents strongly agreed (0.53%), and the rest (0.47%) disagreed. Regarding motivation for compliance with leadership, 8 respondents strongly agreed (0.53%), and the rest (0.47%).